2020
DOI: 10.1037/apl0000463
|View full text |Cite
|
Sign up to set email alerts
|

Liar! Liar! (when stakes are higher): Understanding how the overclaiming technique can be used to measure faking in personnel selection.

Abstract: Aside from consulting fees, charged by a university, for the administration and scoring of the assessments of the Firefighter applicants in Study 1, the authors received no financial support for the research, authorship, or publication of this article. A percentage of the profit of commercial use of the HEXACO-PI-R is used by the Vrije Universiteit Amsterdam to support research by Reinout E. de Vries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 76 publications
6
50
2
2
Order By: Relevance
“…In the original OCQ (OCQ-150; Paulhus et al, 2003), participants were asked to rate their familiarity with 150 items by rating them on a scale ranging from "never heard of it" to "know it very well". Since then, the OCT and a variety of OCQs were developed and used in psychological research (e.g., Atir et al, 2015;Dunlop et al, 2017Dunlop et al, , 2019Mesmer-Magnus et al, 2006;Pennycook & Rand, 2019;Ziegler et al, 2013). Although alternative assessment methods of overclaiming are interesting, we will not further discuss them here and will instead focus on competing scoring methods of conventional OCQs.…”
Section: Scoring Methods Of Overclaiming: Raw Responses Vs Signal Dementioning
confidence: 99%
See 4 more Smart Citations
“…In the original OCQ (OCQ-150; Paulhus et al, 2003), participants were asked to rate their familiarity with 150 items by rating them on a scale ranging from "never heard of it" to "know it very well". Since then, the OCT and a variety of OCQs were developed and used in psychological research (e.g., Atir et al, 2015;Dunlop et al, 2017Dunlop et al, , 2019Mesmer-Magnus et al, 2006;Pennycook & Rand, 2019;Ziegler et al, 2013). Although alternative assessment methods of overclaiming are interesting, we will not further discuss them here and will instead focus on competing scoring methods of conventional OCQs.…”
Section: Scoring Methods Of Overclaiming: Raw Responses Vs Signal Dementioning
confidence: 99%
“…Paulhus and colleagues (2003) concluded that the OCT is useful to assess the proneness to selfenhance, which would be a useful instrument in various contexts that rely on self-report measures (e.g., personnel selection), as these frequently suffer from various biases (Van Vaerenbergh & Thomas, 2013;Ziegler, 2015). Generally, engaging in overclaiming has been described as a potentially economical marker for positivity biases or self-enhancement tendencies (e.g, Bensch et al, 2017;Dunlop et al, 2019;Paulhus et al, 2003). It has been considered as a type of remedy and an efficient mean of assessing individual differences in the tendency to systematically misrepresent oneself in self-reports (Ludeke & Makransky, 2016;Paulhus et al, 2003;Paulhus & Harms, 2004).…”
Section: Claims About Overclaimingmentioning
confidence: 99%
See 3 more Smart Citations